THE POSITION OF THE DPRD VIEWED FROM THE PERSPECTIVE LEGAL POWER AND POSITION OF THE STATE - Haki, Robertus B Oe (Faculty of Law, Khairun University, 2023)
This article aims to find out the concept of the position of the DPR in the perspective of the law of state power and position. Specifically, that law has an important meaning for power because law can act as a means of legalizing the formal power of state institutions, especially the position of the DPR through establishing a legal basis (rules of law) and playing a role in controlling power so that its implementation can be accounted for logically and ethically. The research method used in this paper is normative legal research using a conceptual approach. The results of the study show that the position of the DPRD as a state position is the essence of the limitation of state power by law, in this case the provisions of the laws and regulations governing it as a manifestation of the nature of Indonesia as a state based on law (rechts staat) not based on power (machts staat) as the mandate of the 1945 Constitution which is the legal basis and measure of the performance of state power and positions in all state power institutions, namely the legislature, executive and judiciary. Legal restrictions on the authority of the DPRD office through Law Number 17 of 2014 concerning the MPR, DPR, DPD, DPRD are normatively sufficient, but the limitation on the term of office of the DPRD is still considered not to reflect the principle of equality with provisions regarding other elected political terms. through the mechanism of direct election by the people..